How can health systems approach reducing health inequalities? An in-depth qualitative case study in the UK - Charlotte Parbery-Clark; Lorraine McSweeney; Joanne Lally; Sarah Sowden (BMC, 2024)
Abstract Background Addressing socioeconomic inequalities in health and healthcare, and reducing avoidable hospital admissions requires integrated strategy and complex intervention across health systems. However, the understanding of how to create effective systems to reduce socio-economic inequalities in health and healthcare is limited. The aim was to explore and develop a system's level understanding of how local areas address health inequalities with a focus on avoidable emergency admissions. Methods In-depth case study using qualitative investigation (documentary analysis and key informant interviews) in an urban UK local authority. Interviewees were identified using snowball sampling. Documents were retrieved via key informants and web searches of relevant organisations. Interviews and documents were analysed independently based on a thematic analysis approach. Results Interviews (n = 14) with wide representation from local authority (n = 8), NHS (n = 5) and voluntary, community and social enterprise (VCSE) sector (n = 1) with 75 documents (including from NHS, local authority, VCSE) were included. Cross-referenced themes were understanding the local context, facilitators of how to tackle health inequalities: the assets, and emerging risks and concerns. Addressing health inequalities in avoidable admissions per se was not often explicitly linked by either the interviews or documents and is not yet embedded into practice. However, a strong coherent strategic integrated population health management plan with a system's approach to reducing health inequalities was evident as was collective action and involving people, with links to a "strong third sector". Challenges reported include structural barriers and threats, the analysis and accessibility of data as well as ongoing pressures on the health and care system. Conclusion We provide an in-depth exploration of how a local area is working to address health and care inequalities. Key elements of this system's working include fostering strategic coherence, cross-agency working, and community-asset based approaches. Areas requiring action included data sharing challenges across organisations and analytical capacity to assist endeavours to reduce health and care inequalities. Other areas were around the resilience of the system including the recruitment and retention of the workforce. More action is required to embed reducing health inequalities in avoidable admissions explicitly in local areas with inaction risking widening the health gap.